Variable-Structure Approaches Analysis, Simulation, Robust Control and Estimation of Uncertain Dynamic Processes - Rauh, Andreas; Senkel, Luise; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This edited book aims at presenting current research activities in the field of robust variable-structure systems. The scope equally comprises highlighting novel methodological aspects as well as presenting the use of variable-structure techniques in industrial applications including their efficient implementation on hardware for real-time control. The target audience primarily comprises research experts in the field of control theory and nonlinear dynamics but the book may also be beneficial for graduate students.
Sliding Mode Control for Continuous ans Discrete Time Systems -- Sliding Mode State Estimation for Control Purposes -- Variable-Structure Methods and Models in Control and Estimation.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Mathematical optimization; Calculus of variations; Computer simulation; Mathematics -- Data processing; Control engineering; Multibody Systems and Mechanical Vibrations; Calculus of Variations and Optimization; Computer Modelling; Computational Mathematics and Numerical Analysis; Control and Systems Theory